A case report on Kyrle’s disease in patient with diabetes mellitus - P., Yashmeen Nikhat; Kumar, Jutla V.; Kesavulu, Chennasamudram C. (International Journal of Research in Dermatology, 2024)
Kyrles disease classified under acquired perforating dermatosis, is a rare skin condition predominantly affecting 30-50-year-old females. Characterized by pruritic hyperkeratotic and ulcerated nodules, the disease involves the transepidermal clearance of aberrant endogenous components, leading to inflammatory reactions and expulsion of keratin and cellular material. The etiology though not fully understood, suggests changes in dermal connective tissue may play a role. In case report, a 56-year-old male with type II diabetes mellitus presented knee pain and 3 mm papules on lower limbs. Laboratory findings revealed hematological and metabolic abnormalities, and a skin biopsy confirmed Kyrle’s disease features. Laboratory reports indicated abnormalities in hematology, blood glucose, lipid profile, hepatic and renal function. Biopsy results confirmed acanthosis, hyperkeratosis, dysplsia and granulomatous inflammation. The association of Kyrle’s disease and metabolic abnormalities, emphasizing diabetes and chronic renal failure. Potential pathways involve oxidative damage, endoplasmic stress, and vasculopathy. Treatment options include keratolytics, emollients, antihistamines. Kyrle’s disease often linked to diabetes and chronic renal failure, is a chronic condition with variable remission periods. Early detection and appropriate management are crucial for improving patients’ quality of life. Understanding the association with metabolic abnormalities guides effective therapeutic approaches for this rare dermatological condition.